2020
DOI: 10.5539/ijbm.v16n1p92
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Innovation on Profitability of Jordanian Services Companies

Abstract: This research paper attempts to reveal the level of innovation types in Jordanian services companies. It also investigates the relationship between the overall innovation and profitability in these services companies. Innovation types have been measured through a questionnaire distributed to the members of Securities Depository Center SDC - Public Shareholding Companies – Service Sector. Profitability has been measured through the mean of net profits after taxes for the two years 2018 and 2019. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Product development innovation may come from numerous factors, including the customer's economic status, which affects their demand, and accessible technology (Kristinae et al, 2020). Continuous innovation is needed for product growth, attracting, and retaining customers, which boosts business profitability (Alkhawaldeh, 2020). Schleper et al (2021) revealed that SMEs have used supply chain management strategies that can better adapt to rapid changes during the pandemic.…”
Section: Perceived Effectiveness Of Innovative Strategies Of Social E...mentioning
confidence: 99%
“…Product development innovation may come from numerous factors, including the customer's economic status, which affects their demand, and accessible technology (Kristinae et al, 2020). Continuous innovation is needed for product growth, attracting, and retaining customers, which boosts business profitability (Alkhawaldeh, 2020). Schleper et al (2021) revealed that SMEs have used supply chain management strategies that can better adapt to rapid changes during the pandemic.…”
Section: Perceived Effectiveness Of Innovative Strategies Of Social E...mentioning
confidence: 99%